PENGEMBANGAN e-MODUL MEKANIKA GRANULAR BERBASIS GOOGLE SITES UNTUK MEMFASILITASI PEMAHAMAN KONSEP MAHASISWA - Safitri, Dea Fahmi; Linuwih, Suharto; Yulianti, Dwi (Universitas PGRI Sumatera Barat, 2026)
Granular Mechanics not taught directly in the core curriculum of physics majors because this field is still considered interdisciplinary advanced study. This study aims to develop a Google Sites-based Granular Mechanics e-Module that is feasible, practical, and has the potential to facilitate students' conceptual understanding. This study uses the Research and Development (R&D). However, this study only stops at the development stage. The limited trial subjects in this study were 36 students of the Physics and Physics Education Study Programs. The results showed that the e-Module obtained a material expert validation percentage of 84.43% with a valid category and a media expert validation percentage of 89.55% with a very valid category. The results of the practicality test obtained a percentage of 91.42% with a very practical Based on these results, the Google Sites-based Granular Mechanics e-Module was deemed feasible, practical, and has the potential to facilitate students' conceptual understanding.